Faster Homomorphic Operations and Beyond: Expediting Homomorphic Computation via Boolean Circuit Optimization - Yu, Mingfei; De Micheli, Giovanni (Journal of cryptology, 2026)
Fully homomorphic encryption (FHE) enables secure data processing without compromising data access. However, its computational cost and slower execution compared to plaintext operations present significant challenges. The increasing interest in FHE-based secure computation underscores the need to accelerate homomorphic computations. Existing research predominantly focuses on reducing the multiplicative depth (MD) of FHE circuits, as a lower MD enhances the execution efficiency of each homomorphic operation. However, this often comes at the expense of increased multiplicative complexity (MC), leading to more homomorphic multiplications — a computationally intensive task. Currently, there is a lack of approaches that effectively balance the trade-off between MD reduction and MC increase, potentially resulting in sub-optimal outcomes. This paper addresses this critical gap with three main contributions: (a) an exact synthesis paradigm for generating optimal FHE circuit implementations, (b) a heuristic circuit optimization algorithm, named MC-aware MD minimization, that leverages the exact synthesis paradigm to optimize FHE circuits efficiently, and (c) an FHE circuit optimization flow that integrates MC-aware MD minimization with existing MD reduction techniques. Experimental results demonstrate a 21.32% average reduction in homomorphic computation time and highlight significantly improved efficiency in circuit optimization.